(3gcPG NdbJ (B:s (3bUI (B/s - (3GdQcjHj, YHO Gddgs; (3gjcds ((3GdLRGFQ (B:s (3ehae ddfTQh GdJhRjY (B;(3GdeDSSI GdhWfjI ddafhf GdeWHYjI ,s, 1989)
(3jYGdL bVjI GdeQGI aj GdeOjfI ceG YGdLgG ef bHd GdQja aGNJGQ HWdI gPg GdbUI cj jUa ef NdGdgG eTGYQ h ZQGFR JVQH HLPhQgG aj GYeGb GdfaS GdHTQjI aj TJi GdYUhQ h GdGRefIs
Keywords: (3GdeQCI s; (3GdeQCI GdQjajIs; (3QhGjI s